Cytological diagnosis of amyloidosis presenting as a supraclavicular swelling. Issue 3 (25th November 2019) - Rakheja, Garima; Handa, Uma; Tahlan, Anita; Lehl, Sarabmeet S.
Abstract: Amyloidosis is a well‐recognized entity, that can present as a systemic disease, or, uncommonly, as a localized mass. We report here, a rare presentation of amyloidosis presenting as a supraclavicular swelling, diagnosed on fine‐needle aspiration cytology. Subsequent bone marrow examination led to the diagnosis of multiple myeloma. This case highlights the need to be aware of cytological characteristics of amyloidosis, which can have unusual presentation posing a diagnostic dilemma.